Threats to the Teknaf Wildlife Sanctuary of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
Loss of wildlife, encroachment on forest lands and illegal cutting of trees are the major culprits of management of protected areas (PAs) of Bangladesh. To increase support from local communities and ensure long-term sustainability for Forest PAs in Bangladesh, including Teknaf Wildlife Sanctuary (TWS), community-based conservation approach was introduced by Bangladesh Forest Department. In this study, the effectiveness of forest co-management approach for reducing threats was assessed through key informant interviews, and focus group discussions (FGDs) at TWS. Secondary data were also collected from official document reviews, project reports, journals, books. The study found six direct threats at TWS. Among these, wood collection was the most severe threat. The findings also revealed that, through threat reduction indices, illegal logging, encroachment and hunting, grazing was reduced at a great extent in TWS. We suggest that continuation of co-management of TWS can conserve its natural resources in a sustainable way.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22176 J. Environ. Sci. & Natural Resources, 7(1): 233-239 2014